A World of Disorderly Notions : Quixote and the Logic of Exceptionalism - Hanlon, Aaron R. (Aaron Raymond), 1982- (Book collections on Project MUSE., 2019)
"From Jonathan Swift to Thomas Jefferson, those looking to propose and justify exceptions to social and political norms turned to Cervantes's notoriously mad comic hero as a model, yielding an explosion of imitations of Quixote in fiction and polemical writing; this book examines the exceptionalist character of Quixote and tells the story of how quixotism became political and politicized"--